1987
DOI: 10.2337/diacare.10.2.238
|View full text |Cite
|
Sign up to set email alerts
|

Primary Prevention of Diabetes Mellitus

Abstract: Diabetes mellitus is one of the chronic noncommunicable diseases that have increased markedly in this century. The discovery of insulin and other drugs for lowering hyperglycemia have certainly reduced mortality from acute complications of diabetes and improved the quality of life of many diabetic patients. Recent advances in research into the etiology and natural history of diabetes have increased our knowledge about different types of diabetes to such an extent that primary prevention of diabetes mellitus is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
43
0
1

Year Published

1988
1988
2003
2003

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 92 publications
0
43
0
1
Order By: Relevance
“…The prevention of Type II diabetes has become a major issue both scientifically and from a public health point of view [11]. Type II diabetes has a strong genetic component and hyperglycaemia usually worsens with time [11,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The prevention of Type II diabetes has become a major issue both scientifically and from a public health point of view [11]. Type II diabetes has a strong genetic component and hyperglycaemia usually worsens with time [11,12].…”
mentioning
confidence: 99%
“…The prevention of Type II diabetes has become a major issue both scientifically and from a public health point of view [11]. Type II diabetes has a strong genetic component and hyperglycaemia usually worsens with time [11,12]. When genetically predisposed subjects become more insulin resistant, for instance due to obesity and physical inactivity, they could develop postprandial hyperglycaemia or impaired glucose tolerance (IGT) [13,14].…”
mentioning
confidence: 99%
“…Although the genetic basis of T2DM diabetes has still to be identified, unequivocal evidence shows that obesity and physical inactivity are the main environmental determinants of the disease (2)(3)(4)(5)(6)(7)(8)(9). Subjects with impaired glucose tolerance (IGT) have an increased risk for T2DM and cardiovascular complications of hyperglycemia (10), and therefore form an important high-risk group for actions aimed at preventing diabetes (2)(3)(4)(5).…”
mentioning
confidence: 99%
“…Subjects with impaired glucose tolerance (IGT) have an increased risk for T2DM and cardiovascular complications of hyperglycemia (10), and therefore form an important high-risk group for actions aimed at preventing diabetes (2)(3)(4)(5). Approximately 10 to 15% of the adult populations in developed countries have IGT (2)(3)(4)(5). Chronic hyperglycemia is a necessary condition for microvascular complications such as nephropathy and retinopathy, but it has been recently shown that hyperglycemia is also an independent risk factor for cardiovascular disease (CVD).…”
mentioning
confidence: 99%
See 1 more Smart Citation